2022
DOI: 10.5852/ejt.2022.847.1991
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Odontophrynus (Anura, Odontophrynidae) from the southern portion of the Mantiqueira mountains

Abstract: Using an integrative approach (morphology of the adult and larvae, bioacoustics, osteology, karyotype, and molecular data), we described a new tetraploid species of Odontophrynus to the Mantiqueira mountain range, in southeastern Brazil. The data suggest that Odontophrynus toledoi sp. nov., O. juquinha and Odontophrynus sp. (aff. juquinha) comprise a clade with specimens distributed along three distinct mountain ranges in Brazil: Mantiqueira (O. toledoi sp. nov.) and Espinhaço (O. juquinha) mountains, both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Although geographic variation in advertisement call of anurans was demonstrated in conspecific population of several species (e.g., Castellano et al 2000, Pröhl et al 2007, Baraquet et al 2015, we could not determine if this is the case here with only these data. Conversely, the pulsatile character of the note emitted by M. alipioi promptly distinguishes Macrogenioglottus from the pulsed note found in Odontoprynus and Proceratophrys species (Nascimento et al 2019and references therein, Magalhães et al 2020, Mira-Mendes et al 2020and references therein, Simões et al 2020, Rosset et al 2021, Santana et al 2021, Moroti et al 2022. The release call was also similar to that described by Mira-Mendes et al (2020), with the spectral and temporal parameters overlap (dominant frequency 387.60-559.90 Hz against 430.7 Hz in our sample and duration of the call of 0.032-0.314 s against 0.2-0.3 s in our sample) also suggesting that they belong to the same nominal taxon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although geographic variation in advertisement call of anurans was demonstrated in conspecific population of several species (e.g., Castellano et al 2000, Pröhl et al 2007, Baraquet et al 2015, we could not determine if this is the case here with only these data. Conversely, the pulsatile character of the note emitted by M. alipioi promptly distinguishes Macrogenioglottus from the pulsed note found in Odontoprynus and Proceratophrys species (Nascimento et al 2019and references therein, Magalhães et al 2020, Mira-Mendes et al 2020and references therein, Simões et al 2020, Rosset et al 2021, Santana et al 2021, Moroti et al 2022. The release call was also similar to that described by Mira-Mendes et al (2020), with the spectral and temporal parameters overlap (dominant frequency 387.60-559.90 Hz against 430.7 Hz in our sample and duration of the call of 0.032-0.314 s against 0.2-0.3 s in our sample) also suggesting that they belong to the same nominal taxon.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lisboa et al (2011) reported some differences in relation to the population studied by Abravaya and Jackson but did not discuss it in the context of the family Odontophrynidae. Ten of the 11 species of Odontophrynus have their larvae described (Nascimento et al 2013and references therein, González et al 2014, Menegucci et al 2016, Costa et al 2017, Rocha et al 2017, Santos et al 2017a, Moroti et al 2022. In Proceratophrys, on the other hand, for 21 of the 42 known species the larvae have been described (Provete et al 2017and references therein, Santos et al 2017b, Dias et al 2018.…”
Section: Larval Developmentmentioning
confidence: 99%